Children's right to social protection in the Middle East and North Africa Region - An analysis of legal frameworks from a child rights perspective - Charlotte Bilo; Anna Carolina Machado (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
Although in the past decade the Middle East and North Africa (MENA) region has made important advances in terms of reducing extreme poverty and improving health, education and child survival indicators, progress has remained uneven across the region. Countries affected by conflicts and humanitarian situations (such as Iraq, Libya, Syria and Yemen) in particular have seen a reversal in child well-being indicators (UNICEF 2017a). In fact, child poverty in the region remains a critical concern. According to a recent study in 11 Arab countries, one in four children suffers from acute multidimensional poverty (LAS et al. 2017).
Keywords: 330; Children; right; social protection; MENA; analysis; legal; framework; child; rights; perspective